How much local fiscal autonomy do cities have? A comparison of eight cities around the world. - Slack, Enid (My University, 2017)
Local fiscal autonomy is the extent to which local governments rely on locally raised revenues for funding (rather than receiving transfers from federal or provincial governments) and on their ability to set their own tax rates. A comparison of Toronto, London, Paris, Berlin, Frankfurt, Madrid, Tokyo, and New York reveals that municipal expenditure responsibilities differ among the eight cities; municipal taxes (including local taxes and shared taxes) per capita differ; and, not surprisingly, the extent of local fiscal autonomy also differs. Benefits of tax autonomy include greater efficiency and accountability in the public sector. Tax autonomy gives voters some ability to decide on tax levels and, in that way, taxpayers are more aware of public-service outcomes. Moreover, for these eight cities, there appears to be a relationship between dependence on own-source revenues and the size of the metropolitan economy, with a couple of exceptions. Toronto is less dependent on intergovernmental transfers than many other major cities but, with the exception of London, it has fewer tax options than the other cities. New York is less reliant on state transfers and can levy many different taxes, although the City still needs state permission to implement some new taxes. Tokyo and Paris rely heavily on own-source revenues, but may not have much control over their tax sources. Frankfurt and Berlin have access to more tax sources than many of the other cities, but a portion of these are shared taxes over which they have no tax rate-setting ability. Madrid relies relatively heavily on property taxes but also shares in revenues from the personal income tax, value-added tax, and selected excise taxes. Canadian cities rely largely on the property tax and, although it is a good tax for local governments, it does not grow as the economy grows; it is also highly visible and politically contentious. Moreover, it is not the most appropriate tax to pay for social services or social housing. A mix of taxes would give large Canadian cities more fiscal autonomy, the flexibility to be internationally competitive, and the ability to respond to changing economic and political conditions.
Keywords: Kommunalfinanzen; Selbstverwaltung; Autonomie; Haushaltswesen; Öffentliche Einnahmen; Steuer; Finanzordnung; Städtevergleich; Internationaler Vergleich; Finanzhoheit